2019
DOI: 10.1177/1066896919884647
|View full text |Cite
|
Sign up to set email alerts
|

Be Aware of a Potential Pitfall in Oral and Dental Specimens: Alvogyl Fibers

Abstract: Alvogyl dressing is used to help control hemostasis, foster healing, and prevent complications after certain oral procedures. It is a paste composed of different antiseptic and analgesic substances, and fern-derived Penghawar djambi fibers that have styptic properties. It is claimed to be a resorbable and self-eliminating paste with little complications. However, some studies have demonstrated detrimental effects. We report 3 cases of postextraction nonhealing sockets after Alvogyl dressing. Histologically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Eugenol, an essential oil extracted from various plants, including cloves, possesses exceptional pain-relieving qualities 43 . Alveogyl consistency is provided by the penghawar djambi, a byproduct of Cibotium barometz tree fibers 44 , 45 , which also offers hemostatic properties and ensures easy adherence to soft tissues in the correct dimensions 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eugenol, an essential oil extracted from various plants, including cloves, possesses exceptional pain-relieving qualities 43 . Alveogyl consistency is provided by the penghawar djambi, a byproduct of Cibotium barometz tree fibers 44 , 45 , which also offers hemostatic properties and ensures easy adherence to soft tissues in the correct dimensions 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have suggested that Alveogyl might extend wound healing in alveolar osteitis treatment. Additionally, three reported cases indicated that Alveogyl caused an unexplained foreign body reaction 26 , 27 . Therefore, evaluating novel natural materials and comparing their effectiveness to the widely used Alveogyl is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians routinely rely on biomaterials for implant site development procedures 15,17,18 . However, investigators have associated various biomaterials with impaired healing and unfavorable outcomes in some patients 19–22 …”
Section: Discussionmentioning
confidence: 99%
“…15,17,18 However, investigators have associated various biomaterials with impaired healing and unfavorable outcomes in some patients. [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…An increased threshold for thermal pain as well as an increase in the production of adenosine triphosphate and anti-inflammatory cytokines ( 33 ). The advantages ( 25 , 31 , 34 - 36 ) and disadvantages ( 35 - 37 ) of each treatment are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%